2014
DOI: 10.14503/thij-13-3917
|View full text |Cite
|
Sign up to set email alerts
|

Current Use of Fractional Flow Reserve: A Nationwide Survey

Abstract: Major medical society guidelines recommend the measurement of fractional flow reserve (FFR) C oronary angiography has been well established as the initial invasive technique for evaluating coronary stenoses in patients with stable coronary artery disease (CAD), but its ability to determine the functional significance of an angiographically intermediate lesion is quite limited. Indeed, flow through a stenotic vessel is affected by multiple factors that cannot be measured by visual evaluation alone, such as fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 16 publications
0
13
0
4
Order By: Relevance
“…Recent reports suggest physiologic assessment of coronary artery disease (CAD) prior to revascularization is low despite guidelines supporting its use [1,2]. In prior work, we found <10% of Medicare beneficiaries undergoing elective percutaneous coronary intervention (PCI) received fractional flow reserve (FFR) or equivalent physiological measurements [3].…”
mentioning
confidence: 99%
“…Recent reports suggest physiologic assessment of coronary artery disease (CAD) prior to revascularization is low despite guidelines supporting its use [1,2]. In prior work, we found <10% of Medicare beneficiaries undergoing elective percutaneous coronary intervention (PCI) received fractional flow reserve (FFR) or equivalent physiological measurements [3].…”
mentioning
confidence: 99%
“…Previous studies have shown an increase in the use of FFR since the seminal FAME study, focusing on practice from 2001 to 2013. [25][26][27][28][29] Indeed, more than 70% of physicians thought that the FAME trial led to more widespread use of FFR. 25 Harle et al 29 found a very low rate of FFR; nonetheless, they observed an increasing trend in use over the course of the study period.…”
Section: Discussionmentioning
confidence: 99%
“…A survey conducted in 2012 among 1089 interventional cardiologists identified lack of availability (47%) and problems with reimbursement (39%) as the primary reasons for the infrequent use of FFR guidance (40). In Germany, however, FFR measurement is included in the diagnosis-related group (DRG) system.…”
Section: Reasons For the Infrequent Use Of Ffr Measurementmentioning
confidence: 99%